2013
DOI: 10.1186/1475-9276-12-63
|View full text |Cite
|
Sign up to set email alerts
|

The social determinants of multimorbidity in South Africa

Abstract: Introduction: Multimorbidity is a growing concern worldwide, with approximately 1 in 4 adults affected. Most of the evidence on multimorbidity, its prevalence and effects, comes from high income countries. Not much is known about multimorbidity in low income countries, particularly in sub-Saharan Africa. The aim of this study was to determine the prevalence of multimorbidity and examine its association with various social determinants of health in South Africa.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

22
145
4
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 106 publications
(172 citation statements)
references
References 46 publications
22
145
4
1
Order By: Relevance
“…Despite difficulties that have been mentioned in systematic reviews regarding comparisons of the prevalences of multimorbidity in different countries, 7,38 the prevalence of multimorbidity of 33.1% that we observed in our study was close to the prevalences found in developed countries such as the Netherlands, 39 Canada 13 and Australia, 40 but it was considerably higher than in other LMIC countries. [19][20][21] As expected, the prevalence of multimorbidity increased with age and was higher among women than among men, across educational levels. Both obesity and smoking status showed high prevalence in the study population and these had significant relationships with the outcome, albeit in different ways.…”
Section: Discussionsupporting
confidence: 69%
See 2 more Smart Citations
“…Despite difficulties that have been mentioned in systematic reviews regarding comparisons of the prevalences of multimorbidity in different countries, 7,38 the prevalence of multimorbidity of 33.1% that we observed in our study was close to the prevalences found in developed countries such as the Netherlands, 39 Canada 13 and Australia, 40 but it was considerably higher than in other LMIC countries. [19][20][21] As expected, the prevalence of multimorbidity increased with age and was higher among women than among men, across educational levels. Both obesity and smoking status showed high prevalence in the study population and these had significant relationships with the outcome, albeit in different ways.…”
Section: Discussionsupporting
confidence: 69%
“…For example, the prevalence of multimorbidity was found to be only 4% among South African adults and 70% of them were women. 19 For this reason, considering that the construct of multimorbidity measures not only the current health status of a population but also the health inequalities inherent to the healthcare system, it is crucial to understand the complexity of this phenomenon. Moreover, beyond these absolute inequalities, there is a relative difference among people relating to the way in which they interact with healthcare services, and this relates both to healthcare professionals and to patients.…”
Section: Women Menmentioning
confidence: 99%
See 1 more Smart Citation
“…Individuals with multimorbidity, especially the elderly, tend to experience a greater number of hospitalizations, use multiple medications simultaneously and thereby increase their susceptibility to adverse effects. Thus, the presence of multimorbidity increases the risk of mortality, generates physical and mental problems [3][4][5] and negatively influences quality of life [7][8][9] . It therefore results in greater demands on health care, representing a major challenge for health systems around the world 10,11 , especially as the care involved is more complex 12 .…”
Section: Introductionmentioning
confidence: 99%
“…The prevalence of multimorbidity among elderly persons is high (50 to 98%) 10,11 and its occurrence is associated with advanced age, the female gender, a low socioeconomic level and an unhealthy lifestyle 14,15 . In addition, studies indicate that self-perception of health is often described as negative, due to the occurrence of social, physical or mental disabilities, thus impairing quality of life 8,9,16,17 . The topic is highly relevant, as clinical studies of the elderly often include comorbidity 11 and information on multimorbidity provides support for the improvement of therapeutic strategies.…”
Section: Introductionmentioning
confidence: 99%